USING STEAM AS AN ALTERNATIVE MOTIVE FLUID IN THE EXISTING TURBINE EJECTOR SYSTEM OF THE LJUBLJANA DISTRICT HEATING PLANT - Strušnik, Dušan; Avsec, Jurij (Journal of Energy Technology, 2024)
In this paper, we will examine the possibility of using steam as an alternative motive fluid in the existing turbine ejector system of the Ljubljana district heating plant. As alternative motive fluid, steam is of lesser quality and has constant pressure. The ejector pump system will be adjusted to new circumstances. The purpose of the present work is to rationalise and increase the reliability of ejector system operation at the lowest possible investment costs. A computer model of an ejector model will be designed using the measurements and analyses of the existing system. On the basis of the results obtained, the changes required for the reliable operation of the system using steam as an alternative fluid will be defined and the appropriate solutions will be indicated.